2009
DOI: 10.1097/mao.0b013e3181b76b3b
|View full text |Cite
|
Sign up to set email alerts
|

Younger- and Older-Age Adults With Unilateral and Bilateral Cochlear Implants

Abstract: Objective Compare results of cochlear implantation in younger and older adults in the domains of disability and handicap, as well as in tests of word recognition and localization, across unilateral implant (CI), bilateral (CI+CI) and CI with an acoustic hearing aid in the non-implanted ear (CI+HA). Design Three parts: retrospective (post-implant only) analysis; prospective (pre-versus post-implant); correlation between age and benefit from CI versus CI+CI. Two age groups, above and below 60 years, for the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 25 publications
(35 reference statements)
7
76
0
5
Order By: Relevance
“…That is, some studies have demonstrated that older implanted adults perform lower on SIN than younger implanted adults (Lin, Thorpe, Gordon-Salant, & Ferrucci, 2011;Roberts et al, 2013) yet others have reported that age-related differences are absent (Budenz, et al, 2011;Friedland et al, 2010, Orabi et al, 2006Poissant et al, 2008). Adding to the complexity of aging effects on implant use are studies such as Noble et al (2009) Ventry & Weinstein, 1982), the Hearing Handicap Questionnaire (HHQ; Noble, Tyler, Dunn, & Bhullar, 2008), and Speech, Spatial, and Qualities of Hearing Scale (SSQ; Gatehouse & Noble, 2004). Results showed age-related differences on the SSQ but only with the bilateral CI group and not the bimodal CI+hearing aid group.…”
Section: Age-related Performance Differences Among Adults With Cismentioning
confidence: 99%
See 2 more Smart Citations
“…That is, some studies have demonstrated that older implanted adults perform lower on SIN than younger implanted adults (Lin, Thorpe, Gordon-Salant, & Ferrucci, 2011;Roberts et al, 2013) yet others have reported that age-related differences are absent (Budenz, et al, 2011;Friedland et al, 2010, Orabi et al, 2006Poissant et al, 2008). Adding to the complexity of aging effects on implant use are studies such as Noble et al (2009) Ventry & Weinstein, 1982), the Hearing Handicap Questionnaire (HHQ; Noble, Tyler, Dunn, & Bhullar, 2008), and Speech, Spatial, and Qualities of Hearing Scale (SSQ; Gatehouse & Noble, 2004). Results showed age-related differences on the SSQ but only with the bilateral CI group and not the bimodal CI+hearing aid group.…”
Section: Age-related Performance Differences Among Adults With Cismentioning
confidence: 99%
“…The benefits of improved audibility and speech recognition are expected to cascade into other areas of life such as the patient's social, psychological, and overall physical health. In fact, studies unanimously demonstrate significantly higher health-related quality of life (HRQoL) scores among older CI users at postoperative compared with preoperative intervals (Djalilian et al, 2002;Noble, Tyler, Dunn, & Bhullar, 2009;Orabi, Mawman, Al-Zoubi, Saeed, & Ramsden, 2006;Park, Shipp, Chen, Nedzelski, & Lin, 2011;Poissant, Beaudoin, Huang, Brodsky, & Lee, 2008;Vermeire et al, 2005).…”
Section: Existing Studies Of Older CI Listenersmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-assessment questionnaires provide subjective data that enable practicing professionals the knowledge of difficulties in hearing impaired patients in specific daily (17) situations, allowing CI mapping in the rehabilitation process in accordance with different technologies and performance of each individual in particular. One can minimize or even solve some of these difficulties in order to provide the CI users a better quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…O implante coclear se tornou um tratamento cada vez mais comum e eficaz para as pessoas com deficiência auditiva profunda pós-lingual e cada vez mais as pesquisas mostram que os usuários deste dispositivo podem atingir melhorias significativas em suas habilidades auditivas (LEUNG et al, 2005;COELHO et al, 2009;NOBLE et al, 2009 Nos adultos com perda auditiva pós-lingual um fator importante a ser considerado é o tempo de privação sensorial. As pesquisas mostram que quanto menor o tempo de vida com a deficiência auditiva, maiores escores de reconhecimento da fala serão alcançados em pouco tempo no pós-operatório.…”
Section: Resultados Com Implante Coclear Em Adultosunclassified